Recourse in Digital Financial Services : Opportunities for Innovation - Mazer, Rafe; Garg, Nitin (World Bank, Washington, DC, 2016)
This actual case highlights the importance of an efficient customer recourse system. Recourse systems can help consumers overcome the challenges related to product adoption and continued use by helping resolve initial problems or challenges quickly, which can build trust in providers and their products, and increase uptake and customer retention. Effective recourse, and the key principles of awareness, access, timeliness, and fairness associated with effective recourse systems, becomes all the more relevant in the case of digital financial services (DFS), which still face trust deficits among some consumers.